Plan de negocio para la creación de una hamburguesería artesanal con enfoque gastronómico global en la ciudad de Santa Marta (2022)
This business plan directs its approach towards the creation of an artisan hamburger restaurant with a global gastronomic focus, in the city of Santa Marta. In Colombia, the consumption of food outside the home has increased and consumers are always looking for different food alternatives, therefore, it is expected to offer different types of hamburgers with unique flavors, incorporating ingredients from different countries around the world. The company proposed in this business plan points to the development of an innovation scheme as a central value, using a framework of good service, and incorporating an optimal customer service model through rapid response schemes through dual channels. of attention. This research has a mixed approach, it is expected to know the perception of consumers from primary instruments, and in the same way, secondary sources will be used to strengthen each of the sections of this document from the theoretical and methodological conception.